2017
DOI: 10.3389/fvets.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

When Yawning Occurs in Elephants

Abstract: Yawning is a widely recognized behavior in mammalian species. One would expect that elephants yawn, although to our knowledge, no one has reported observations of yawning in any species of elephant. After confirming a behavioral pattern matching the criteria of yawning in two Asian elephants (Elephas maximus) in a zoological setting, this study was pursued with nine captive African elephants (Loxodonta africana) at a private reserve in the Western Cape, South Africa, the Knysna Elephant Park. Observations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
(18 reference statements)
1
9
0
Order By: Relevance
“…The results from our nighttime observations, with three instances of contagious yawning meeting the specific criteria, expand upon and confirm our previous report of intraspecific contagious yawning between elephants (20). There were two instances where a standing elephant yawned in response to an arousing elephant yawning and one from a standing elephant yawning in response to another standing elephant yawning.…”
Section: Intraspecific Contagious Yawningsupporting
confidence: 88%
See 2 more Smart Citations
“…The results from our nighttime observations, with three instances of contagious yawning meeting the specific criteria, expand upon and confirm our previous report of intraspecific contagious yawning between elephants (20). There were two instances where a standing elephant yawned in response to an arousing elephant yawning and one from a standing elephant yawning in response to another standing elephant yawning.…”
Section: Intraspecific Contagious Yawningsupporting
confidence: 88%
“…Control observations from the previous study showed that spontaneous yawns were unlikely to occur outside of the two-minute period following arousal from a recumbency. As described in our previous study (20), a yawn is characterized as a slow opening of the jaw, a brief frozen open posture and a quick closure of the jaw opening. This behavior is seen most clearly in the attached video clip (Supplementary Video 2) of the elephant yawning in response to a handler yawning.…”
Section: Intraspecific Yawning Observationsmentioning
confidence: 81%
See 1 more Smart Citation
“…At a private reserve in the Western Cape, South Africa, a study was conducted on captive elephants where it was found that they also yawn and that this behaviour may be associated with stimulation from nighttime recumbencies [76].…”
Section: Physical and Behavioural Characteristicsmentioning
confidence: 99%
“…For example, within the hominid family, yawn contagion has been shown in chimpanzees (Campbell & Cox, 2019; Campbell & de Waal, 2011), bonobos (Palagi et al., 2014) and humans (Provine, 2005) but not in gorillas (Palagi et al., 2019), thus suggesting that phylogenetic closeness cannot necessarily predict, per se, yawn contagion (Palagi et al., 2020). Outside the primate order, evidence of contagious yawning are reported for dogs and wolves (Neilands et al., 2020; Romero et al., 2013, 2014; Silva et al., 2012), Asian and African elephants (Rossman et al., 2017; Rossman et al., 2020), sheep (Yonezawa et al., 2017), elephant seals (Wojczulanis‐Jakubas et al., 2019) and parrots (Gallup et al., 2015; Miller et al., 2012). The occurrence of yawn contagion may be linked to the level of attention and responsiveness to conspecifics' stimuli.…”
Section: Introductionmentioning
confidence: 99%